The Relationship Between Nutritional Status (BMI) and Age at Menarche Among Junior High School Adolescent Girls - Filza Yudrika (Indonesian Journal Publisher, 2026)
Menarche is the first menstrual period experienced by adolescent girls. In recent decades, the age of menarche has tended to occur earlier, which may negatively affect health. Nutritional status, measured by Body Mass Index (BMI), is considered an important factor influencing the age of menarche. This study aimed to determine the relationship between nutritional status (BMI) and age at menarche among adolescent girls at SMPN 3 Sungai Penuh. This quantitative study used a cross-sectional design and was conducted from July to August 2025. A total of 97 adolescent girls were selected using proportional random sampling. Data were collected through measurements of height and weight and questionnaires, and analyzed using the Chi-square test. The results showed that most respondents had a normal age of menarche (81.4%) and normal nutritional status (63.9%). Statistical analysis indicated a significant relationship between BMI and age at menarche (p = 0.000). In conclusion, nutritional status is significantly associated with age at menarche among adolescent girls. Maintaining normal nutritional status is important to support healthy reproductive development.